2012
DOI: 10.1021/jf301139h
|View full text |Cite
|
Sign up to set email alerts
|

Multispectroscopic and Molecular Modeling Approach To Investigate the Interaction of Flavokawain B with Human Serum Albumin

Abstract: Interaction of flavokawain B (FB), a multitherapeutic flavonoid from Alpinia mutica with the major transport protein, human serum albumin (HSA), was investigated using different spectroscopic probes, i.e., intrinsic, synchronous, and three-dimensional (3-D) fluorescence, circular dichroism (CD), and molecular modeling studies. Values of binding parameters for FB-HSA interaction in terms of binding constant and stoichiometry of binding were determined from the fluorescence quench titration and were found to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
64
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 198 publications
(74 citation statements)
references
References 45 publications
(97 reference statements)
8
64
0
Order By: Relevance
“…9. The strong peak 1 (λ ex = 280 nm, λ em = 358 nm), mainly revealed the spectral characteristics of tryptophan and tyrosine residues and reflected changes in the tertiary structure of BSA, and peak 2 (λ ex = 220 nm, λ em = 358 nm), mainly exhibited the fluorescence characteristic of polypeptide backbone structures and reflected changes in the secondary structure of BSA (49)(50)(51). Peaks 3 and 4 meant the Rayleigh scattering peak (λ ex = λ em ) and the second-order scattering peak (2λ ex = λ em ), respectively.…”
Section: Conformational Investigationsmentioning
confidence: 99%
“…9. The strong peak 1 (λ ex = 280 nm, λ em = 358 nm), mainly revealed the spectral characteristics of tryptophan and tyrosine residues and reflected changes in the tertiary structure of BSA, and peak 2 (λ ex = 220 nm, λ em = 358 nm), mainly exhibited the fluorescence characteristic of polypeptide backbone structures and reflected changes in the secondary structure of BSA (49)(50)(51). Peaks 3 and 4 meant the Rayleigh scattering peak (λ ex = λ em ) and the second-order scattering peak (2λ ex = λ em ), respectively.…”
Section: Conformational Investigationsmentioning
confidence: 99%
“…The participation of these intermolecular forces in the binding of 6-shogaol to HSA is well-supported by the structural features of 6-shogaol, which possesses both apolar and polar characteristics (Figure 1). As suggested in earlier reports (Caruso et al, 2014;Feroz et al, 2012Feroz et al, , 2013Molina-Bolivar et al, 2014;Neamtu, Tosa, Bogdan, 2013), it is not possible to account for the observed thermodynamic parameters according to a single intermolecular-force model. Therefore, the energetics data obtained in this study seem to reflect the collective contributions of hydrophobic interactions, van der Waals forces and hydrogen bonds in 6-shogaol-HSA complexation.…”
Section: Resultsmentioning
confidence: 94%
“…While no obvious change in the emission maxima (310 nm) was observed upon addition of W 3 (or W 4 ) when Δλ was 15 nm, synchronous fluorescence spectra obtained with Δλ=60 nm showed a blue shift from 348 to 340 nm upon W 3 (or W 4 ) addition. The observed blue shift signified a transition of the Trp residues from a polar to a less polar environment [6]. Results suggested that binding of W 3 (or W 4 ) to FTO had little effect on the microenvironment around Tyr residues but was sufficient to perturb the environment in the vicinity of the lone Trp residue from polar to slightly nonpolar.…”
Section: Synchronous Fluorescencementioning
confidence: 98%
“…Thus, the study on the interactions of ligands with proteins is important in understanding the action of these molecules in the body [6]. The nature and magnitude of drug-protein interaction significantly influences the biological activity of the drug.…”
Section: Introductionmentioning
confidence: 99%